2017
DOI: 10.1097/bpo.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Routine Postoperative Radiographs After Pinning of Pediatric Supracondylar Humerus Fractures

Abstract: Level IV-case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
1
21
0
3
Order By: Relevance
“…Karalius et al 16 evaluated the utility of obtaining early (seven to ten days postoperative) and late (prior to pin pull) radiographs. These authors concluded that early radiographs were of value, as 1.6% of patients had an alteration in management based on these radiographs, including revision surgery, early pin removal and pin adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Karalius et al 16 evaluated the utility of obtaining early (seven to ten days postoperative) and late (prior to pin pull) radiographs. These authors concluded that early radiographs were of value, as 1.6% of patients had an alteration in management based on these radiographs, including revision surgery, early pin removal and pin adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Our study similarly demonstrated no changes to the management of patients based on follow up radiographs and, while not directly tested given its retrospective design, this questions the value of routine radiographs in the absence of repeat injury or worsening exam findings. One wonders whether these patients can be spared routine monitoring radiographs, similar to a recommendation following pediatric supracondylar humerus fractures ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the accepted fragment size and distance to humerus were depended on the surgeon’s experience and lack of accurate assessment, which was a limitation of our study. A computed tomography (CT) scan or MRI may be helpful for more accurate assessment, but whether such a need exists remains to be discussed [ 13 ].…”
Section: Discussionmentioning
confidence: 99%